Calcium Addition Improving Pectin Level in Oil Palm Seedlings (Elaeis guineensis Jacq.) - Nurwahyuni, Endah; Eka Tarwaca Susila Putra (Jurnal Penelitian Kelapa Sawit, 2020)
Long drought due to climate anomalies results in physiological damage to oil palm which is characterized by frond fracture to the decreased productivity. One of the efforts to increase the resistance of oil palm to drought is through the addition of calcium. This study aimed to determine the effect of calcium on hormonal changes (as secondary messenger), the rate of photosynthesis till the content of pectin as a reinforcing component of cell walls which is expected to reduce the risk of frond fracture due to drought. The treatment was arranged in factorial 3 x 4 in the random complete block design (RCBD) split-plot. The first factor was the dose of calcium application which was 0 (control/without calcium), 0,04 g, 0,08 g, and 0,12 g. The second factor was the intensity of drought stress consisting of severe stress, moderate stress, and control/field capacity with an intensity of one week after achieving target weight. Data that fulfilled the assumptions of homogeneity and normality were then analyzed using variance analysis at a level of accuracy of 5% and continued with DMRT. The results showed that calcium can increase the resistance of oil palm seeds through increased GA content, decreased ABA content and increased photosynthetic rates in all soil moisture conditions, but varied according to the intensity of drought.